Perfil epidemiológico dos acidentes ofídicos ocorridos de 2001 a 2021, no estado do Pará, Brasil - Cunha, Paola Ferreira (2023)
Ophidism or ophidian accident is the clinical picture resulting from the inoculation of a venom. Considered by the World Health Organization as a neglected tropical disease, which mainly affects the rural population, it is a little evidenced problem with low priority in public health. In Brazil, there is a great diversity of snake species, but only two families are of clinical interest, the Elapidae family and the Viperidae family. The objective of this work is to trace the epidemiological profile of snakebites in the state of Pará during the years 2001 to 2021, under the influence of climatic factors. For this analysis, it was necessary to identify the average number of snakebites over the years and relate it to the rainfall corresponding to the analyzed period, identify the incidence of accidents in the six mesoregions of the state, identify the number of accidents by genus of snakes, use the genus of snakes to classify cases as mild, moderate and severe, show the evolution of cases (cure, death, sequel) for each type of snake, the relationship between the time elapsed between the bite and medical care with the mortality rate, verify the profile of victims such as gender, age, education and race of people who suffer the accident. The study area was the state of Pará located in the northern region, composed of 144 cities, with a territorial area of 1,245,870.707km², an estimated population of 8,777,124 people. Its climate is hot and humid, with a very stable thermal regime. The study used secondary data available on the DATASUS platform. For the analysis of these data, information was considered, which correspond to snakebite accidents that occurred exclusively in the municipalities of the state of Pará, grouped and distributed in six mesoregions, such as the relative frequencies and absolute frequencies of each studied group, data on the genera of the snakes involved , evolution of cases, age, gender, schooling and race of human beings involved in accidents. Only the state of Pará has 99,294 cases notified as snakebites, being the first state in number of victims. Rainfall is significantly correlated with the mean frequency of snakebites (rs 0.9062; p < 0.0001). The highest incidence occurred in the mesoregion of southwest Pará. Regarding snakes, it was observed that the genus Bothrops are the ones that attack the most, but the genus Micrurus presents higher rates of serious accidents, the genus Crotalus presented the highest number of victims with sequelae after the accident and the genus Lachesis the highest number of deaths. A relationship was observed between the length of service and case fatality (rs= -0.3000; p=0.6238). The profile of the state of Pará after the study was male, aged between 20 and 39 years old, 4 to 7 years of schooling completed, predominant brown race. However, the statistics of snakebites in Brazil are still hampered by the fact that many snakebites are not identified or ignored.